PROTECTION OF VICTIMS OF HUMAN RIGHTS VIOLATIONS - Yusuf DM, Mohd.; Nofarizal, Dedi; Putra, Fransiskus; Hutagaol, Hendra Dm; Monarchi, Try Krisna (Sekolah Tinggi Ilmu Hukum Awang Long, 2024)
The crime of genocide is often associated with crimes against humanity but when viewed in depth the crime of genocide is different from crimes against humanity, where the crime of genocide is aimed at groups such as nations, races, ethnicities or religions while crimes against humanity are aimed at citizens and civilians. The demand for the resolution of cases of human rights violations has prompted the birth of Law Number 39 of 1999 concerning Human Rights which was later followed by Law Number 26 of 2000 concerning the Human Rights Court which is intended to answer various problems of human rights violations, especially gross human rights violations. Article 7 of the Human Rights Court Law states that the crime of genocide is a crime that violates gross human rights because it is committed by killing, causing severe suffering, extermination, coercion by groups and even the forcible transfer of children from one group to another. Thus the human rights court law expressly provides threats to the perpetrators. The method used is normative legal research. Based on the results of the research, it is known that the Crime of Genocide and its Implications in Law Number 39 of 1999 concerning Human Rights that the crime of genocide is one of the most serious forms of human rights violations, involving systematic efforts to destroy certain groups based on ethnicity, religion, or race. Law No. 39/1999 on Human Rights has not specifically and in detail regulated the crime of genocide and the elements of the crime. This has led to a lack of a strong and comprehensive legal framework to prosecute perpetrators of genocide, as well as provide justice and legal certainty for victims.